Social welfare and coercion in public finance - Stanley L. Winer; George Tridimas; Walter Hettich (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper develops an expanded framework for social planning in which the existence of coercion is explicitly acknowledged. Key issues concern the precise definition of coercion for individuals and in the aggregate, its difference from redistribution, and its incorporation into normative analysis. We explore modifications to traditional rules for optimal fiscal policy in the presence of coercion constraints and determine the degree of coercion implied by traditional social planning. The paper maps the trade-off between social welfare and aggregate coercion and explores its implications for normative policy and the comparative evaluation of institutions, including competitive democracy.
Keywords: D70; H10; H20; H21; 330; Coercion; redistribution; social planning; optimal fiscal policy; marginal cost of funds; public goods; collective choice; Sozialpolitik; Öffentliches Gut; Einkommensteuerpolitik; Public Choice; Soziale Wohlfahrtsfunktion; Theorie